LEGAL PROTECTION FOR HOLDERS OF DEPOSITS AS A FORM OF INVESTMENT AVAILABLE IN BANK - Supriyadi, Ahmad (International Peneliti Ekonomi, Sosial dan Teknologi, 2024)
Legal protection is something that is very important considering that banks are financial institutions which in all their activities cannot be separated from the role of their customers, because the legal relationship between customers and banks is a legal relationship created based on trust (fiduciary relationship). A Certificate of Deposit or Certificate of Deposits is a product issued by a bank as a securities tool or instrument used to make payments in a transaction. Therefore, to foster public trust in banking institutions, steps need to be taken to protect the interests of depositors so that time deposit funds stored in a bank are guaranteed to be safe from all risks that may arise in the future. Providing legal protection to depositors is also related to the bank's operational potential. The formulation of the problem is what is the position of issuing deposit certificates in banking? and what form of legal protection is required by deposit holders in carrying out legal relations with banks?The form of research used in the research is normative juridical research. The results of this research are that the position of issuing deposit certificates is regulated in more detail in terms of the position of deposit certificates as securities that can be owned by all binding persons and their issuance can be reviewed from Financial Services Authority Regulation Number 10 /PJOK.03/2015 concerning the issuance of Deposit Certificates by Banks where deposit certificates can be issued in the form of scripless or scripless. AndThe legal relationship between the bank and the depositor is that they are essentially bound by an agreement where each party has the rights and obligations to fulfill the contents of the agreement. With the existence of an agreement, a relationship exists between the bank and the customer, where this relationship must be maintained by each party, especially the bank, by paying attention to the principles, namely the principle of trust, the principle of confidentiality, and the principle of prudence. Based on the provisions of Article 1 number 5 of Law Number 10 of 1998, between banks and customers is regulated by agreement law. So that the basis of the legal relationship between the bank and the customer is a contractual relationship. This means that once a customer enters into a contractual agreement with the bank, the engagement that arises is an engagement based on a contract (agreement).